Stories from Abakwa. - Nyamnjoh, Francis B. (African Studies Centre research series., 2007)
Childhood and growing up in Mimboland, Cameroon are infused with fascinating stories and adventures. Discover life in Abakwa with Tom and his friend, as they are chased through an orchard for secretly harvesting avocadoes and mangoes. Smile as Mathias Chi's overloaded canoe almost loses balance. Shiver as Roland runs through the dark streets and bleeding corridors of Mvog Mvog. And cry when Big Brother discovers how his siblings suffered when he was away at school. What happens to Esther when she finds the courage to make an announcement at the Abakwa Mountain Foot Radio Station about her husb.